Arthroscopic Decompression and Bone Grafting of Proximal Humeral Intraosseous Ganglion. Issue 1 (March 2015) - McCrum, Christopher L.; Yi, Anthony; Omid, Reza
<x xml:space="preserve">Abstract</x> Intraosseous ganglia are rare lesions that can cause pain and leave patients susceptible to pathologic fracture. To date, these lesions have been treated with curettage and bone grafting through an open approach, although more recent techniques have allowed arthroscopic treatment of lesions located at the wrist, knee, and ankle. We present a novel, arthroscopic technique to treat intraosseous ganglion lesions of the proximal humerus. Using an arthroscopic approach, these lesions can be visualized, decompressed and curettage, with the ability to evaluate the extent of pathologic tissue remaining. This approach also allows for identification and treatment of additional glenohumeral pathology. Furthermore, we present a novel, completely arthroscopic technique of bone grafting and compaction to fill the resultant void.